Stability and Release Kinetics of an Advanced Gliclazide-Cholic Acid Formulation: The Use of Artificial-Cell Microencapsulation in Slow Release Targeted Oral Delivery of Antidiabetics - Mooranian, Armin; Negrulj, Rebecca; Mathavan, Sangeetha; Martinez, Jorge; Sciarretta, Jessica; Chen-Tan, Nigel; Mukkur, Trilochan; Mikov, Momir; Lalic-Popovic, M.; Stojancevic, M.; Golocorbin-Kon, S.; Al-Salami, Hani (Springer New York LLC, 2014)
Introduction: In previous studies carried out in our laboratory, a bile acid (BA) formulation exerted a hypoglycaemic effect in a rat model of type-1 diabetes (T1D). When the antidiabetic drug gliclazide (G) was added to the bile acid, it augmented the hypoglycaemic effect. In a recent study, we designed a new formulation of gliclazide-cholic acid (G-CA), with good structural properties, excipient compatibility and exhibits pseudoplastic-thixotropic characteristics. The aim of this study is to test the slow release and pH-controlled properties of this new formulation. The aim is also to examine the effect of CA on G release kinetics at various pH values and different temperatures. Method: Microencapsulation was carried out using our Buchi-based microencapsulating system developed in our laboratory. Using sodium alginate (SA) polymer, both formulations were prepared: G-SA (control) and G-CA-SA (test) at a constant ratio (1:3:30), respectively. Microcapsules were examined for efficiency, size, release kinetics, stability and swelling studies at pH 1.5, pH 3, pH 7.4 and pH 7.8 and temperatures of 20 and 30 °C. Results: The new formulation is further optimised by the addition of CA. CA reduced microcapsule swelling of the microcapsules at pH 7.8 and pH 3 at 30 °C and pH 3 at 20 °C, and, even though microcapsule size remains similar after CA addition, percent G release was enhanced at high pH values (pH 7.4 and pH 7.8, p < 0.01). Conclusion: The new formulation exhibits colon-targeted delivery and the addition of CA prolonged G release suggesting its suitability for the sustained and targeted delivery of G and CA to the lower intestine.